ANALISIS PERHITUNGAN TOTAL PRODUKTIVE MAINTENANCE (TPM) MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) DI PT ABC - Handayani, Putri; Suseno Suseno (KAMPUS AKADEMIK PUBLISING, 2026)
The pulp and paper industry is required to maintain high levels of production machine effectiveness to achieve sustainable production targets. PT ABC operates the Pulp Making unit continuously for 24 hours; however, operational issues such as downtime, quality degradation, and unmet production targets still occur. This study aims to analyze the effectiveness of machine performance in the Pulp Making 2 unit using the Overall Equipment Effectiveness (OEE) method as an implementation of Total Productive Maintenance (TPM). This research employs a quantitative method by processing production data from January to June 2025. The analyzed data include machine operating time, planned and unplanned downtime, production output, and defective products. The OEE value is calculated based on three main components: availability, performance efficiency, and quality rate. The results show that the average availability of 93% and performance efficiency of 98% have met the standards set by the Japan Institute of Plant Maintenance (JIPM). However, the quality rate of 97% is still below the JIPM standard of 99%. Overall, the OEE value reaches 88% and is classified as world-class performance, although there remains potential effectiveness loss arising from product quality issues and machine downtime .